2013
DOI: 10.1186/1471-2296-14-49
|View full text |Cite
|
Sign up to set email alerts
|

Early Dementia Questionnaire (EDQ): A new screening instrument for early dementia in primary care practice

Abstract: BackgroundWorldwide, the population is ageing, resulting in an associated increase in dementia prevalence. Forgetfulness in elderly people is often perceived as normal in some local cultures and thus, the early detection of dementia in primary care requires detection of symptoms other than memory complaints.This study was conducted to screen elderly patients for early dementia in primary care using a newly developed Early Dementia Questionnaire (EDQ) and comparing it with a standard assessment tool, the Mini M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“… 23 GPs could be supported in the diagnostic process by better validation of existing instruments, or the development of new tools that are culturally and educationally appropriate. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 23 GPs could be supported in the diagnostic process by better validation of existing instruments, or the development of new tools that are culturally and educationally appropriate. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Preliminary study of this new tool had shown that it is a simple, easy to administer and user friendly tool for screening of early dementia [12]. During this study, a few words were deleted from the original questionnaire (question 11 and 15) based by the response made from the pilot study of 50 respondents to make it clearer without changing the meaning of the questions.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary study on EDQ used 8 or more as the cutoff point to determine whether a patient had possible early dementia [12]. However, in this study a cutoff score of 10 is finally chosen after looking into the ROC curve and the sensitivity and specificity of different scoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations